The Doctor of Nursing Practice: A Sentiment Analysis and Credential Correlation - Lewis, Matthew; Welliver, Mark D; Leach, Stephen (International Journal of Advanced Nursing Studies, 2012)
The Doctor of Nursing Practice (DNP) degree is gaining interest within the nursing profession but not without debate. A review of the literature regarding the DNP demonstrates that the debate focuses on academic, clinical, and professional practice issues of nursing. The multiple debate points and positive and negative perspectives leads one to ask, “do author degree credentials correlate with positive or negative sentiment regarding the DNP?”The points of debate surrounding the DNP were identified from the literature and adapted into a sentiment analysis tool. The tool was used for the extraction of positive or negative sentiment from 90 pieces of DNP and practice doctorate related literature. The positive or negative sentiment expressed by each author was correlated with their credentials. No particular sentiment was found that correlated with non-DNP credentialed authors. However, a correlation was identified between DNP credentialed authors and the expression of positive sentiment toward the DNP.